2016
DOI: 10.1128/jvi.02883-15
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T Follicular Helper Cells Are the Major HIV Reservoir within Central Memory CD4 T Cells in Peripheral Blood from Chronically HIV-Infected Individuals on Combination Antiretroviral Therapy

Abstract: In this study, we examined the peripheral blood (PB) central memory (T CM ) CD4؉ T cell subsets designated peripheral T follicular helper cells (pTfh cells) and non-pTfh cells to assess HIV permissiveness and persistence. Purified pTfh and non-pTfh cells from healthy HIV-negative donors were tested for HIV permissiveness using green fluorescent protein (GFP)-expressing HIV-1NL4-3/Ba-L, followed by viral reactivation using beads coated with anti-CD3/anti-CD28 monoclonal antibodies. The role of pTfh cells in HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 53 publications
6
111
0
1
Order By: Relevance
“…7C). Of note, the frequency of p24-positive cells in reactivated CD4 T cells was similar to other previous reports (57)(58)(59). HIV RNA in the cell culture supernatant was not altered by venetoclax treatment compared to control (Fig.…”
Section: Treatment Of Gfpsupporting
confidence: 76%
“…7C). Of note, the frequency of p24-positive cells in reactivated CD4 T cells was similar to other previous reports (57)(58)(59). HIV RNA in the cell culture supernatant was not altered by venetoclax treatment compared to control (Fig.…”
Section: Treatment Of Gfpsupporting
confidence: 76%
“…Memory T FH can be long-lived and primarily have a central memory phenotype, similar to the resting CD4+ T cell reservoir that harbors the majority of HIV DNA in treated individuals [50]. One recent study reported that the majority of HIV-1 DNA in peripheral blood was harboured by central memory T FH in subjects with sustained virologic suppression on ART [54]. Nevertheless, the precise phenotype of peripheral T FH is somewhat controversial [55] and until an accurate phenotype is determined, identifying the role of T FH in the latent HIV reservoir using peripheral blood will be challenging.…”
Section: Follicular Hiv Reservoirs During Treated Diseasementioning
confidence: 99%
“…These new data demonstrate that lymph node cells harboring viral DNA permit productive infection even in the presence of suppressive cART. The very rare T FH in blood also contribute to the HIV reservoir in patients receiving cART (134).…”
Section: Lymph Nodesmentioning
confidence: 99%